The clock of ages : why we age--how we age--winding back the clock - Medina, John, 1956- (Cambridge University Press, 1996)
Anyone who has watched the wrinkles of time develop on their face, or has been disturbed by a loss of memory, has uncomfortably confronted the human aging process. The inexorable march of time on our bodies begs an important question: why do we have to grow old? Written in everyday language, The Clock of Ages takes us on a tour of the aging human body - all from a research scientist's point of view. From the deliberate creation of organisms that live three times their natural span to the isolation of human genes that may allow us to do the same, The Clock of Ages also examines the latest discoveries in geriatric genetics. Sprinkled throughout the pages are descriptions of the aging of many historical figures, such as Florence Nightingale, Jane Austen, Bonaparte and Casanova. These stories underscore the common bond that unites us all: they aged, even as we do. The Clock of Ages tells us why.